Clean And Green City Program: Program Kota Bersih Dan Hijau - Roudhotul Mufaridah, Siti; Fitria Agustina, Isna (Indonesian Journal of Public Policy Review, 2022)
The Clean and Green Sidoarjo Program in Kepuh Kemiri Village in addition to overcoming existing environmental problems, also aims to develop public awareness to care about the surrounding environment and change people's behavior not to throw garbage in any place, process waste into economic value. The use of a qualitative approach to the writing method. Methods of collecting data through interviews, field observations, and documentation. The collection of two types of data, primary data and secondary data. The author uses the data analysis method : data collection, data reduction, data presentation, and reasoning. From the results of this paper, the implementation of the Clean and Green Sidoarjo program has been running according to predetermined indicators, although there are several obstacles faced.